KUDUMBASHREE A Poverty Eradication Mission in Kerala - A K PAT (Economic and Political Weekly November 26, 2005, 2005)
A recent survey on the performance of the Kudumbashree projects a poverty eradication mission the Kerala government initiated in 1999 - shows some deficiencies and lacunae in a few selected panchayats in certain factors. But, still, it would seem that Kudumbashree with its accent on the empowerment, participation and leadership of women could make a qualitative difference to the life of people.